Slip Rate of Kumering Fault in Lampung Province Calculated from GPS Data from 2007 to 2021 - Satrio Muhammad Alif; Putri Ferlia Cahyani; Ongky Anggara; Aditya Rizqiansyah (Universitas Diponegoro, 2022)
Kumering Fault in Lampung Province is a segment of SFZ that was tectonically active region that had generates large earthquakes. The earthquake hazard around Kumering Fault can be estimated by understanding slip rate of Kumering Fault. This research aim is to estimate slip rate of Kumering Fault by using GPS data from 2007 to 2021. GPS data used in this research are 6 periodic GPS sites and 1 continuous Sumatran GPS Array site. GPS data is processed to obtain daily solution coordinates which are used to calculate velocity by using least-square method of linear regression. Fault parallel velocities are calculated to estimate slip rate and locking depth of Kumering Fault. The The process to obtain slip rate is using grid-search method by finding best fit velocities for all GPS sites. The velocities of GPS sites indicate Sundaland Plate movement. Fault parallel velocities shows the typical movement of right-lateral Kumering Fault. The slip rate of Kumering Fault estimated from this study is 18.2 ± 10 mm/year while the locking depth of the Kumering Fault is 17 ± 3 km. It proves that SFZ is rigid block. However, building more GPS sites in area study is mandatory to obtain better result.